Acoustic characteristics of Chinese first-level vowels production by Kazakh learners - Zhao, Zhongxing; Mahfoodh, Omer Hassan Ali; Boh, Phaik Ean (Penerbit Universiti Kebangsaan Malaysia, 2024)
Kazakhstan, a Central Asian country, boasts a rich and diverse linguistic landscape, with Kazakh as its official language. The objective of this study was to analyze the acoustic characteristics of seven Chinese first-level vowels produced by Kazakh learners. Fourteen Kazakh learners of Mandarin Chinese were recruited, and the acoustic data obtained from these participants were meticulously compared. Each participant was recorded while producing the seven Chinese vowels, with each utterance being repeated nine times to ensure consistency and reliability. This rigorous approach aimed to minimize variability and ensure the accuracy of the findings. The acoustic data were then analyzed using Mini-Speech Lab software, focusing on extracting the formant frequencies (F1 and F2) of the seven vowels. The analysis revealed that Kazakh learners encountered significant challenges in producing apical vowels, while they exhibited no difficulty in articulating high vowels. The linguistic background of Kazakhstan, where both Kazakh and Russian phonetic systems differ significantly from Mandarin, might contribute to the specific challenges faced by Kazakh learners in mastering Mandarin vowels. The study offers important implications for the development of effective instructional strategies aimed at improving vowel production in Kazakh learners of Chinese, thereby enhancing their overall language acquisition process.